Heating : CIBSE guide B1 : 2016. (Chartered Institution of Building Services Engineers, 2016)
Chapters B1 to B4 address issues relating to specific services. There are usually several possible design solutions to any situation, and the Guide does not attempt to be prescriptive but rather to highlight the strengths and weaknesses of different options. This document, which forms chapter 1 of CIBSE Guide B, deals with the selection, design, commissioning, operation and management of most types of heating systems in buildings. It deals specifically with nondomestic buildings though much of the contents will apply to domestic communal heating. Such systems provide space (including ventilation) heating and/or hot water services and installations such as swimming pools. Virtually every building (outside the tropics), contains a heating system. In most cases its primary purpose is to produce acceptable levels of thermal comfort - paramount for the health and wellbeing of building occupants and provide domestic hot water - or to protect the building fabric or its contents.
"PDF amended November 2016 to incorporate corrections to pages 1-27, 1-30, 1-71, 1-76, 1-89, 1-90, 1-99, 1-100, 1-106, 1-119, 1-129."
Keywords: Heating -- Design and construction.; Heating -- Handbooks, manuals, etc.; elektronické knihy; electronic books